A glimpse through the origin, composition and biomedical applications of green tea and its polyphenols: A review - Joseph, Suja; Nallaswamy, Deepak; S, Rajeshkumar; Dathan, Pradeep; Ismail, Shahin; Jacob, Jose; Rasheed, Nazia (Plant Science Today, 2024)
Green tea is an aromatic healthy beverage that is the least processed type of tea, containing numerous bioactive components beneficial to humans. It is produced from the plant Camelia sinensis, a shrub native to Asia. This article reviews the literature review on the origin, manufacturing, composition, biomedical applications and health benefits of green tea and its polyphenols. The main bioactive components of green tea are polyphenols, primarily flavonoids. Catechins are the main flavonoids present in tea. These high-potential compounds can stimulate certain enzymes and alter cellular functions by preventing the oxidation of biomolecules due to their antioxidant properties. The catechins found in tea include (-) –epicatechin (EC), (-) epigallocatechin (EGC), (-)-epicatechin-3-gallate (ECG) and epigallocatechin -3-gallate (EGCG). Epigallocatechin gallate (EGCG) is the most prominent catechin in fresh leaves, constituting around 50-60 % of the flavonoids. EGCG is the active component with significant health benefits. These catechins contribute to therapeutic actions and the prevention of infections. Recent research on green tea suggests various applications based on its medicinal value to reduce the risk of many diseases.